The Application of the Problem-Based Learning Cooperative Model to Improve Sociology Learning Outcomes on the Concept of Social Conflict : (In Class X-2 of SMA Negeri 2 Taniwel, West Seram Regency) (International Journal of Education and Literature, 2025)
The era of globalization is an era of quality competition, where only thosebwith high competence will be able to compete in the free market. Therefore, developing high-quality human resources is something that cannot be compromised. Education that supports development in this era is education that can foster students’ potential’ enabling them toface and overcome life’s challenges. Thus, in the learning process, teachers should not only serve as models or sources of knowledge but also act as learning managers. As learning managers, teachers play an important role in creating a learning environment that allows students to learn confortably and effectively. Based on observations at SMA Negeri 2 Taniwel, it was found that students in class X-2 have low learning outcomes in sociology. The writer’s observation in class indicated that sociology learning was dominated by lecture methods, resulting in students being less active during the learning process. According to research conducted by Al Muchtar (1991), learning in social studies education does not sufficiently simulate students to be actively involved in the learning process. Furthermore, the teaching and learning process of social studies carried out bye teachers has not been able to faster a learning culture among students, wich in turn significantly affects their learning achievement and outcomes. To support active learning strategies, teachers can apply various relevant learning models. Therefore, the learning process will become more varied, innovative, and constructive, creating interaction between teachers and students, among students themselves, and between students and other learning resources.